Wykorzystanie promocji w kreowaniu konkurencyjności gminy - Nowacki, Robert (Use of Promotion in Creation of Municipality's Competitiveness, 2007)
In today's world, competition among self-governmental units acquires greater importance. They use the instruments of territorial marketing in order to raise their attractiveness and competitiveness whose expression is the ability to acquire investment capital, budgetary means, EU assistance funds, skilled personnel, or involvement of private persons, being a source of income of municipalities and entities operating in their territory. Promotional policy of a key importance among those instruments. It serves building an image of self-governmental units and is a way for a direct impact on potential customers. Its effects are evaluated in a different manner, and an authentic verifier of efficacy is municipality's competitiveness against the background of the entire region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 719-729